PERBEDAAN EFEK MINUMAN BERKARBONASI DENGAN MINUMAN PROBIOTIK TERHADAP PERUBAHAN GAYA Z-SPRING - saragih, jean; Muttaqin, Zulfan; LINA HADI, LINA (Jurnal FARMASIMED (JFM), 2021)
The effect of the drink can cause changes in the resilience of the wire which is usually due to carbonated drinks or probiotics Carbonated beverage is a daily drinks with carbonic acid and has pH of 2.32. Carbonated beverage with lower pH may cause the releasing of nickel (Ni) and chromium (Cr) ions on stainless steel orthodontic wire in oral cavity and result in alteration of resilience. Purpose: The aim of this research is to know the change of resilience of stainless steel removable orthodontic wire before and after immersion with ,probiotic,carbonated beverages and saline solution. Material and methods: This study is true experimental study using pre and post test with control group design, consist of 9 treatment groups and control groups were obtained from preliminary test, each group using stainless steel ortodontic wire with the diameter is 0.6 mm and given a scratch along the wire then perform the resilience before and after the immersion using a UTM. Each sample was immersed and put in an incubator at 37oC for the first 4 days then measured with a UTM device then soaked again for the next 4 days and measured again. Research result: The results showed that there were differences in the resilience of the wires on day 0 and day 4 when immersed in carbonated drinks (p = 0.047) compared to soaking saliva and probiotics. Then z-spring stainless steel orthodontic wire soaked in probiotic obtained p value = 0.038. This shows that there is a difference in the resilience of the 8th day compared to the 0th day.Conclusion: Results Soaking stainless steel orthodontic wire changes its resilience. There was a significant difference between day 4 and day 8 for the wire soaked in carbonated drinks (p = 0.001). there is no significant difference in the wire soaked with probiotic drinks.